2019
DOI: 10.1111/avj.12906
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, cause, outcome and possible risk factors associated with facial nerve paralysis in dogs in a Sydney population (2001–2016): a retrospective study

Abstract: Objective This study aims to assess the incidence and causes of facial nerve paralysis (FNP) in dogs in the Sydney region. Its outcome and possible risk factors are investigated to prognosticate and aid design of diagnostic and treatment plans.Design Retrospective case study.Methods Client-owned dogs presented to the University Veterinary Teaching Hospital, Sydney (UVTHS), between 2001 and 2016 with FNP were included (n = 122). The incidence of each cause of FNP was investigated. A reference population of nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The presence of facial nerve paralysis or Horner's disease usually indicates an underlying cause of peripheral vestibular dysfunction such as otitis media/interna, 48 therefore documenting these deficits can help veterinary practitioners in differentiating between central and peripheral VD. Moreover, cases with idiopathic facial nerve paralysis can present with vestibular signs 34 . In our study, 2/7 cases diagnosed with otitis media or interna had Horner's syndrome reported (1 of which also had facial nerve palsy) and 3/14 cases diagnosed with IPVD had facial nerve palsy reported.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The presence of facial nerve paralysis or Horner's disease usually indicates an underlying cause of peripheral vestibular dysfunction such as otitis media/interna, 48 therefore documenting these deficits can help veterinary practitioners in differentiating between central and peripheral VD. Moreover, cases with idiopathic facial nerve paralysis can present with vestibular signs 34 . In our study, 2/7 cases diagnosed with otitis media or interna had Horner's syndrome reported (1 of which also had facial nerve palsy) and 3/14 cases diagnosed with IPVD had facial nerve palsy reported.…”
Section: Discussionsupporting
confidence: 44%
“…In immature dogs, the first presenting sign of syringomyelia could be scoliosis, which can appear similar to a head tilt of vestibular origin 30 . VD in CKCS can be also idiopathic—CKCS is one of the most commonly seen breeds with idiopathic facial nerve paralysis 34 and facial and vestibular neuropathy of unknown origin 35 . Aside from central and IPVD, CKCS are also predisposed to primary secretory otitis media, known to commonly be associated with peripheral VD 3,36 …”
Section: Discussionmentioning
confidence: 99%
“…The most common etiology of facial neuropathy in dogs is idiopathic, accounting for up to 75% of all cases presented with facial neuropathy 3–6 . Diagnosis of idiopathic facial neuropathy is based on neurological signs and exclusion of all other causes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs associated with idiopathic facial neuropathy may result in ipsilateral paresis or plegia of the muscles of facial expression, with or without associated dysfunction of the parasympathetic innervation, depending on the region of the facial nerve affected. Associated ipsilateral clinical signs of peripheral vestibular dysfunction are common and have been reported in between 42 and 65% of patients diagnosed with idiopathic facial neuropathy 3–5 . This is likely explained by the close proximity of the facial and vestibulocochlear nerves at the level of the inner ear within the proximal part of the facial nerve canal, so that swelling of the facial nerve at that level may result in ipsilateral peripheral vestibular syndrome and vice versa 4,6 …”
Section: Introductionmentioning
confidence: 99%
“…Facial paralysis, also known as facial nerve paralysis, is caused by function loss of facial muscle innervated by the seventh cranial nerves in human [1] or even in animals [2]. This facial problem is generally characterized by muscle dysfunction on one side of the face.…”
Section: Introductionmentioning
confidence: 99%